Judge's Decision Regarding Criminal Actions Against Perpetrators of Motor Vehicle Theft (Case Study Decision Number 1396/Pid.B/2023/Pn.Medan) - Simanjuntak, Lehonna; Nainggolan, Tiurma Yuni Firli Kristi; Siahaan, Parlaungan Gabriel; Lumban Batu, Dewi Pika (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted at the Medan District Court by following cases and decisions regarding criminal acts of motor vehicle theft. The results found in this case were that the suspect had been found and taken to legal action and was subject to a criminal offense for 2 years and six months. However, with light sentences and sanctions that are not too heavy, the public will not be more deterred from committing crimes. The method used in this research is a qualitative research method which is closely related to the social definition paradigm.